International Symposium on Oilfield Chemistry 2003
DOI: 10.2118/80206-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hydrophobically Modified Water-Soluble Polymer as a Selective Bullhead System for Water-Production Problems

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractFor many years, bullhead systems have received a great deal of attention from the oil and gas industry. Because of the completion techniques used in many wells, protecting the hydrocarbon interval effectively during a water control treatment is not always practical or cost-effective. Bullhead systems offer the option of a treatment without zonal isolation and are designed to decrease water production with little or no decrease in oil or gas production. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Also, water production can lead to other problems such as corrosion of surface equipment, need for more separator capacity, and other disposal and handling concerns. [1][2][3] Several techniques have been developed to overcome this problem. The most popular involve injection of polymer 1-3, 6-9 or gel 4,5 into the production wells.…”
Section: Introductionmentioning
confidence: 99%
“…Also, water production can lead to other problems such as corrosion of surface equipment, need for more separator capacity, and other disposal and handling concerns. [1][2][3] Several techniques have been developed to overcome this problem. The most popular involve injection of polymer 1-3, 6-9 or gel 4,5 into the production wells.…”
Section: Introductionmentioning
confidence: 99%
“…1. As previously published (Eoff et al 2003(Eoff et al , 2004, numerous laboratory tests have demonstrated the capability of the SFFL system to reduce water-effective permeability with little or no effect on hydrocarbon-effective permeability. In many of the early tests, when this system was injected into cores, a rapid pressure increase was observed.…”
Section: Description Of the Sffl Systemmentioning
confidence: 91%
“…10 This system was shown to provide significant permeability reduction in relatively lowpermeability sandstone cores at 100% water saturation, as well as, at residual oil saturation. The hydrophobically modified, water-soluble polymer described in that paper was found to provide a minimum of 80% brine permeability reduction in sandstone cores in a broad range of permeabilities, while showing minimal effect on oil permeability.…”
Section: Rpm Technologymentioning
confidence: 99%